THE MELODY OF THE TEXT AND THE TEXT OF THE MELODY. WEÖRES – KODÁLY ANALOGIES - CSÁKÁNY, Csilla (Studia Universitatis Babes-Bolyai Musica, 2023)
Sándor Weöres was a significant experimental artist in Hungarian poetry, who often perceived the tonal elements of the Hungarian language as melodies. The musicality of his texts, the rhythmic play of his words finds artistic form in his verses. Zoltán Kodály followed the poet’s poems with 4 4 and literary theory and Sándor Weöres’s affinity for music encouraged a creative-artistic dialogue between the two, which provided the space for a number of masterpieces for both children and adult audience. In our paper, we will look for language-music (text-melody) analogies in Kodály’s works composed to Weöres’ poems.